A review of conventional and innovative-sustainable methods for cleaning reflectors in concentrating solar power plants - Bouaddi, Sahar; Fernández-García, Aránzazu; Sansom, Christopher L.; Sarasua, Jon Ander; Wolfertstetter, Fabian; Bouzekri, Hicham; Sutter, Florian; Azpitarte, Itiziar (MDPI, 2019)
The severe soiling of reflectors deployed in arid and semi arid locations decreases their reflectance and drives down the yield of the concentrating solar power (CSP) plants. To alleviate this issue, various sets of methods are available. The operation and maintenance (O&M) staff should opt for sustainable cleaning methods that are safe and environmentally friendly. To restore high reflectance, the cleaning vehicles of CSP plants must adapt to the constraints of each technology and to the layout of reflectors in the solar field. Water based methods are currently the most commonly used in CSP plants but they are not sustainable due to water scarcity and high soiling rates. The recovery and reuse of washing water can compensate for these methods and make them a more reasonable option for mediterranean and desert environments. Dry methods, on the other hand, are gaining more attraction as they are more suitable for desert regions. Some of these methods rely on ultrasonic wave or vibration for detaching the dust bonding from the reflectors surface, while other methods, known as preventive methods, focus on reducing the soiling by modifying the reflectors surface and incorporating self cleaning features using special coatings. Since the CSP plants operators aim to achieve the highest profit by minimizing the cost of cleaning while maintaining a high reflectance, optimizing the cleaning parameters and strategies is of great interest. This work presents the conventional water-based methods that are currently used in CSP plants in addition to sustainable alternative methods for dust removal and soiling prevention. Also, the cleaning effectiveness, the environmental impacts and the economic aspects of each technology are discussed.
Keywords: sustainable cleaning; CSP reflectors; soiling; dust removal; mirror washing